2009
DOI: 10.1051/0004-6361/200912213
|View full text |Cite
|
Sign up to set email alerts
|

The zCOSMOS redshift survey: the role of environment and stellar mass in shaping the rise of the morphology-density relation from z ~ 1

Abstract: Context. For more than two decades we have known that galaxy morphological segregation is present in the Local Universe. It is important to see how this relation evolves with cosmic time. Aims. To investigate how galaxy assembly took place with cosmic time, we explore the evolution of the morphology-density relation up to redshift z ∼ 1 using about 10 000 galaxies drawn from the zCOSMOS Galaxy Redshift Survey. Taking advantage of accurate HST/ACS morphologies from the COSMOS survey, of the well-characterised z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
148
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(167 citation statements)
references
References 98 publications
17
148
2
Order By: Relevance
“…Many prior studies have found evidence for the quenched fraction of satellites exceeding that of centrals at a fixed stellar mass, particularly at lower stellar masses (e.g., Balogh et al 2004;Cortese et al 2006;Moran et al 2007;van den Bosch et al 2007Tasca et al 2009;Peng et al 2012;Hirschmann et al 2013;Wetzel et al 2013;Bluck et al 2014). Taken together, these studies additionally find that the quenching of satellites depends on environmental parameters, such as local (over-)density, halo mass, location within the halo, galaxy clustering, and combinations of these parameters.…”
Section: Results For Satellitesmentioning
confidence: 70%
See 2 more Smart Citations
“…Many prior studies have found evidence for the quenched fraction of satellites exceeding that of centrals at a fixed stellar mass, particularly at lower stellar masses (e.g., Balogh et al 2004;Cortese et al 2006;Moran et al 2007;van den Bosch et al 2007Tasca et al 2009;Peng et al 2012;Hirschmann et al 2013;Wetzel et al 2013;Bluck et al 2014). Taken together, these studies additionally find that the quenching of satellites depends on environmental parameters, such as local (over-)density, halo mass, location within the halo, galaxy clustering, and combinations of these parameters.…”
Section: Results For Satellitesmentioning
confidence: 70%
“…Some credence to this idea comes from the morphology -density relation (e.g., Dressler et al 1980;Bamford et al 2009;Tasca et al 2009;Capellari et al 2011), whereby galaxies are more bulge dominated (and hence have higher central velocity dispersions) for their stellar masses in denser regions of space. The only way to determine to what extent this explanation can account for satellite galaxy quenching is to measure the dependence of satellite quenching on environment at fixed central velocity dispersion.…”
Section: Results For Satellitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the zCOSMOS 10k catalogue we have already shown (e.g., Tasca et al 2009;Bolzonella et al 2010;Pozzetti et al 2010;Peng et al 2010, among others) that stellar mass is the main driver of the observed dependencies of galaxy properties on the environment. Still the environment playing an important, although secondary, role.…”
Section: Resultsmentioning
confidence: 93%
“…The final sample of 20, 707 objects, the so-called "20k bright", has been assembled providing the needed statistics. In addition, the high spectroscopic sampling rate (∼ 70%) and the complete coverage of the COSMOS field with the Hubble Space Telescope (HST) Advanced Camera for Surveys (ACS) (Koekemoer et al 2007), allows to perform on one side an accurate reconstruction of the density field (Kovač et al 2010) and on the other a robust morphological classification (Tasca et al 2009) and bulge/disk decomposition.…”
Section: Overviewmentioning
confidence: 99%